Up-regulation of CD64-expressing monocytes with impaired FcγR function reflects disease activity in polyarticular psoriatic arthritis. (2nd November 2015) - Matt, P; Lindqvist, U; Kleinau, S
Abstract : Objectives: The aim of this study was to assess monocyte Fc receptor (FcR) status and function in patients with active psoriatic arthritis (PsA) in relation to healthy controls (HC) and to disease activity. Method: The study population comprised 23 patients with active polyarticular PsA and 33 age- and gender-matched HC. Immunoglobulin (Ig) levels, inflammatory laboratory parameters, patient-reported outcomes of joint disease activity, skin scoring (Psoriasis Area and Severity Index, PASI), and joint status were determined in the patients. Monocytes were analysed for the expression of FcRs for IgG (FcγR) class I (CD64), IIa (CD32a), IIb (CD32b), and III (CD16), the FcR for IgA (FcαR) (CD89), and surface-bound IgG. The monocytic FcγR function was assessed by evaluating IgG immune complex (IC) binding and tumour necrosis factor (TNF)-α production following IgG-IC stimulation. The monocytes were further subdivided and analysed according to their CD14 and CD16 expression. Results: The PsA patients presented elevated serum levels of IgG1, 2, and 3 and increased numbers of CD64 + monocytes. Furthermore, the PsA monocytes exhibited increased cell-bound IgG, and the FcγR function was affected in terms of reduced IgG-IC-mediated TNF-α release. These findings correlated significantly with different markers of joint disease activity. PsA was also accompanied by an increase in the CD16 low-expressing monocyte subset. Conclusions: An intensified humoral immune response affects monocytes and their FcR status in active polyarticular PsA. The up-regulated CD64 + monocytes seem to be have an important role in psoriatic joint inflammation. These cells may prove to be a useful target in future PsA therapeutic interventions.